Microvascular endothelial function is impaired in patients with idiopathic hyperaldosteronism. Issue 11 (November 2018) - Kishimoto, Shinji; Matsumoto, Takeshi; Oki, Kenji; Maruhashi, Tatsuya; Kajikawa, Masato; Matsui, Shogo; Hashimoto, Haruki; Kihara, Yasuki; Yusoff, Farina; Higashi, Yukihito
Abstract The aims were to evaluate the relationship between idiopathic hyperaldosteronism (IHA) and grade of vascular function in the macrovasculature and microvasculature. Vascular function, including reactive hyperemia index (RIH), flow-mediated vasodilation (FMD), and nitroglycerine-induced vasodilation (NID) were evaluated in 52 patients with IHA, 53 patients with aldosterone-producing adenoma (APA), and 52 age-, sex-, and blood pressure-matched patients with essential hypertension (EHT). Log RHI was lower in the IHA and APA groups than in the EHT group (0.54 ± 0.25 and 0.55 ± 0.23 versus 0.79 ± 0.28;P  < 0.01, respectively). FMD was lower in the APA group than in the EHT group (3.4 ± 2.1% versus 4.8 ± 2.8%;P  = 0.02), whereas there was no significant difference in FMD between the IHA and the APA and EHT groups. NID was lower in the APA group than in the EHT group (10.0 ± 4.5% versus 12.5 ± 5.7%;P  = 0.03), whereas there was no significant difference in NID between the IHA, APA, and EHT groups. Multiple regression analysis revealed an association of log RHI with plasma aldosterone concentration (t  = −2.24;P  = 0.03) and an association of FMD with plasma aldosterone concentration (t  = −3.07;P  < 0.01). Microvascular endothelial function was impaired in patients with IHA compared with that in patients with EHT.